Kedudukan Memorandum Of Understanding dan Surat Keputusan Bersama Ditinjau dari Teori Perundang-undangan - Zayanti Mandasari (Fakultas Hukum Universitas Islam Indonesia, 2013)
This research emphasizes on the issue on the status of MoU (Master of Understanding) and SKB (Joint Decree) in the perspective of regulatory theories, binding power and implication of MoU and SKB towards the institutions and/or commission issuing it. This is a normative legal research with the secondary data in the form of primary, secondary and tertiary law materials using a regulatory approach. The results of this result then show that: first, SKB (Joint Decree) about the ethic code and Guidelines of Judge Attitude in the perspective of regulatory theory can be categorized as a policy regulation. MoU about the Optimality of Corruption Eradication in the perspective of regulatory theories is not able to be categorized as a part of regulations. Second, the SKB (Joint Decree) has a strong binding power towards MA (Supreme Court) and KY (Judicial Commission). MoU has emerged a binding power to KPK (Committee of Corruption Eradication), POLRI (Indonesian Police) and Kejari (District Attorney) since it is in Agreement is Agreement category that binds all parties. Third, SKB about Ethic Code and Judge Attitude Guidelines emerges an implication that MA and KY must obey SKB that has been made altogether. MoU about the Optimization of Corruption Eradication emerges an implication resembling to Agreement is Agreement. Hence, KPK, Polri and Kejari must obey all agreements.